Adjuvant chemotherapy may have no significant survival benefit in older patients with stage II/III gastric cancer: a multicenter retrospective study - Zheng-Zheng Shen; En-Ze Li; Ruo-Lan Zhang; Meng-Xuan Cao; Yan-Qiang Zhang; Qing Yang; Can Hu; Si-Wei Pan; Zhi-Yuan Xu; Zai-Sheng Ye; Jing-Yang He (Journal of Cancer Research and Clinical Oncology)
Abstract Aim Postoperative adjuvant chemotherapy is known to enhance cure rates and is thus recommended for stages pII to pIII. However, specific guidelines for such treatment in elderly gastric cancer (GC) patients are currently lacking. This study examines the impact of adjuvant chemotherapy on the postoperative survival of these patients. Methods We reviewed a total of 7749 patients with GC who underwent radical gastrectomy at Zhejiang Cancer Hospital and Fujian Cancer Hospital from January 2007 to December 2019. We conducted univariate and multivariate Cox regression analyses to investigate the impact of clinicopathological factors on overall survival (OS) and cancer-specific survival (CSS) in these patients. Additionally, we created a meta-analysis forest plot and employed propensity score matching (PSM) to mitigate confounding bias. Results Age and adjuvant chemotherapy were independent risk factors for OS and CSS. Stratified analysis based on chemotherapy use revealed a statistically significant difference in OS and CSS between younger patients who did and did not receive adjuvant chemotherapy. In contrast, no significant differences in OS and CSS were observed between older patients with or without adjuvant chemotherapy. These findings remained consistent after propensity score matching (PSM). Conclusions Age and adjuvant chemotherapy are independent risk factors for OS and CSS in patients with stage II/III GC; for patients with stage II/III gastric cancer aged ≥ 75 years, shared decision-making should be made taking into account functional status and comorbidities, rather than conventional adjuvant chemotherapy.